Pengembangan Teknologi Metaverse Ekosistem E-Mobility Pada Pameran Teknologi International Berbasis Augmented Reality - Noorlela Marcheta; Dewi Yanti Liliana; Agus Setiawan; Ilham Sidiq; Asep Kurniawan (Jurnal Teknologi Informasi dan Multimedia, 2024)
Augmented Reality (AR) can be used as a new technology in organizing virtual and paperless exhibitions to make the products on display more attractive and updated regularly. This can happen because AR is a technology that integrates the virtual and real worlds. AR has been widely used as a medium to assist in providing information in real-time in an interesting, interactive, and educational way. This journal explains the development of AR media and its feasibility as an international promotional media in introducing the E-Mobility Ecosystem. The E-Mobility Ecosystem is a PENTA-branded convertible electric car, one of PNJ's superior technologies. The Hannover Messe'23 exhibition with the theme "Making Indonesia 4.0" requires products to be displayed in digital form (paperless). Thus, an application is needed to support digital promotion. This research aims to develop a Marker-Based AR application as one of the promotional media for E-Mobility Ecosystem products, which consist of charging stations, electric vehicles, and the Center Of Otomo-tive. The output of this research is an application that can show E-Mobility Ecosystem products by displaying a 3D Model when the mobile camera is directed at a card given an Object marker. This research method uses the Multimedia Development Life Cycle (MDLC). This research has been successfully developed and distributed. This is evidenced by user assessment using a Likert scale with a success rate of 87.8% strongly agree.